Antennal transcriptome analysis of odorant-binding proteins and characterization of GOBP2 in the variegated cutworm Peridroma saucia - Dong, Jun-Feng; Wang, Ke; Sun, Ya-Lan; Tian, Cai-Hong; Wang, Shao-Li (Frontiers in Physiology, 2023)
Odorant-binding proteins (OBPs) are expressed at extremely high concentrations in the chemo-sensilla lymph of insects and have long been thought to be crucial for delivering the semiochemicals to the odorant receptors. They are represented by multiple classes: general odorant-binding proteins (GOBP1 and GOBP2) and pheromone-binding proteins. In the current study, we identified a total of 35 OBPs in the antennal transcriptome of Peridroma saucia, a worldwide pest that causes serious damage to various crops. A gene expression value (TPM, transcripts per million) analysis revealed that seven OBPs (PsauPBP1/2/3, PsauGOBP1/2, PsauOBP6, and PsauOBP8) were highly abundant in the antennae. Next, we focused on the expression and functional characterization of PsauGOBP2. Real-time quantitative-PCR analysis demonstrated that PsauGOBP2 was predominantly expressed in the antennae of both sexes. Fluorescence binding assays showed that the recombinant PsauGOBP2 strongly binds to the female sex pheromone components Z11-16: Ac (Ki = 4.2 μM) and Z9-14: Ac (Ki = 4.9 μM) and binds moderately (6 µM ≤ Ki ≤ 13 µM) to the host plant volatiles phenylethyl acetate, β-myrcene, and dodecanol. Further 3D structural modeling and molecular docking revealed that several crucial amino acid residues are involved in ligand binding. The results not only increase our understanding of the olfactory system of P. saucia but also provide insights into the function of PsauGOBP2 that has implications for developing sustainable approaches for P. saucia management.